1991
DOI: 10.2134/agronj1991.00021962008300030005x
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield and Nutritive Value of Elephantgrass as Affected by Harvest Frequency and Genotype

Abstract: Elephantgrass (Pennisetum purpureum Schum.) is known throughout much of the wet tropics for its prolific growth and usage as a forage for ruminants. In a 3‐yr study conducted on a welldrained, infertile soil (loamy, siliceous, hyperthermic, Grossarenic Paleudult) and under subtropical conditions near Gainesville, FL, the response of this forage to three harvest frequency regimes was measured. Genotypes evaluated were four tall elephantgrasses (PI 300086, ‘Merkeron’, N‐43, and N‐51), a dwarf elephantgrass (Mott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 9 publications
6
34
0
Order By: Relevance
“…Plants hardly suffered from drought stress in both summers, though there was less precipitation in 2000. In normal napiergrass, HDMY decreases with the increase in cutting frequency (Miyagi, 1985;Woodard and Prine, 1991;Sunusi et aL, 1997). Woodard and Prine (1991) reported that the dwarf variety of Mott was less sensitive to the increased cutting frequency than normal varieties, although the two dwarf varieties in the present study were sensitive to cutting frequency.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Plants hardly suffered from drought stress in both summers, though there was less precipitation in 2000. In normal napiergrass, HDMY decreases with the increase in cutting frequency (Miyagi, 1985;Woodard and Prine, 1991;Sunusi et aL, 1997). Woodard and Prine (1991) reported that the dwarf variety of Mott was less sensitive to the increased cutting frequency than normal varieties, although the two dwarf varieties in the present study were sensitive to cutting frequency.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In normal napiergrass, HDMY decreases with the increase in cutting frequency (Miyagi, 1985;Woodard and Prine, 1991;Sunusi et aL, 1997). Woodard and Prine (1991) reported that the dwarf variety of Mott was less sensitive to the increased cutting frequency than normal varieties, although the two dwarf varieties in the present study were sensitive to cutting frequency. This characteristic, insensitive to the cutting frequency may be due to the earlier recovery of ground cover by the leafage after harvest (Gardner et aL, 1985) because of larger TN in dwarf varieties than in normal varieties.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Averaged across two years, yield increased from approximately 20-40 Mg ha -1 yr -1 as the harvest interval was increased from 6 to 24 weeks. The effect of the harvesting interval varies by genotype, but in general long harvest intervals increases DM production and aids persistence (Woodard and Prine 1991;Hanna et al 2004). Harvesting can be accomplished using conventional silage choppers with large heads if the plants are planted in spaced rows.…”
Section: Management and Bioprocessingmentioning
confidence: 99%
“…Dry matter yield and forage quality suitable for biomass use are expected to be variable, dependent on variations in growth attributes among genotypes of napiergrass, as affected by climate and soil factors at the observed site and dependent on the growth stage of herbages (Woodard & Prine, 1991;Ishii et al, 1998). High leaf expansion, vigorous tillering, and rapid dry matter production in tall canopy are categorized as important factors to attain high production of napiergrass (Ferraris et al, 1986;Matsuda et al, 1991;Wadi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%